2021
DOI: 10.1101/2021.02.17.21251867
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of sampling frequency and normalization of SARS-CoV-2 wastewater concentrations for capturing COVID-19 burdens in the community

Abstract: Wastewater surveillance for SARS-CoV-2 provides an approach for assessing the infection burden across a city. For these data to be useful for public health, measurement variability and the relationship to case data need to be established. We measured SARS-CoV-2 RNA concentrations in the influent of twelve wastewater treatment plants from August 2020 to January 2021. Replicate samples demonstrated that N1 gene target concentrations varied by 21% RSD between technical replicate filters and by 14% RSD between dup… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 35 publications
5
25
0
Order By: Relevance
“…For COVID-19 WBE to be useful for public health decision-making, a better understanding is needed of the variability of SARS-CoV-2 in wastewater and how it relates to the true incidence or prevalence of COVID-19 in the contributing population ( McClary-Gutierrez et al, 2021 ). Sources of target signal variability in wastewater include inconsistencies in sample collection and laboratory processing ( Ahmed et al, 2020d ; Feng et al, 2021 ), nucleic acid degradation based on travel time and conditions in the sewer ( Hart and Halden, 2020a ), and signal dilution due to rainfall and diurnal flow changes ( Zahedi et al, 2021 ). Researchers have addressed some of these sources of variability through normalization to biomarkers, increased sampling frequency, processing sample replicates, and smoothing/forecasting ( D'Aoust et al, 2021b ; Feng et al, 2021 ; Graham et al, 2020 ; McLellan et al, 2021 ; Nemudryi et al, 2020 ; Stadler et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For COVID-19 WBE to be useful for public health decision-making, a better understanding is needed of the variability of SARS-CoV-2 in wastewater and how it relates to the true incidence or prevalence of COVID-19 in the contributing population ( McClary-Gutierrez et al, 2021 ). Sources of target signal variability in wastewater include inconsistencies in sample collection and laboratory processing ( Ahmed et al, 2020d ; Feng et al, 2021 ), nucleic acid degradation based on travel time and conditions in the sewer ( Hart and Halden, 2020a ), and signal dilution due to rainfall and diurnal flow changes ( Zahedi et al, 2021 ). Researchers have addressed some of these sources of variability through normalization to biomarkers, increased sampling frequency, processing sample replicates, and smoothing/forecasting ( D'Aoust et al, 2021b ; Feng et al, 2021 ; Graham et al, 2020 ; McLellan et al, 2021 ; Nemudryi et al, 2020 ; Stadler et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the pipeline presented here allowed meta-analysis of the data, revealing the variability present in each step of sample processing. While some amount of variation is due to lower quality or technical error, some appears to be inherent methodological variation or variation in the wastewater itself 27,28 . In the future, modeling the contributions of these variables to overall noise in the data could provide better confidence in the results.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteroides rRNA loads varied more spatially and temporally than crAssphage or PMMoV in this study (Figure 1), but Bacteroides-normalized SARS-CoV-2 N1 had a moderate correlation with clinical testing data ( =0.35). While measurement of Bacteroides rRNA gene in wastewater has been commonly applied for fecal source tracking and Bacteroides rRNA has been targeted to increase assay sensitivity (D'Aoust et al, 2021b;Feng et al, 2021), to our knowledge, no prior raw wastewater values have been reported in the literature for Bacteroides rRNA (Table S10). Similarly, no values were found in the literature for 18S rRNA concentrations in raw wastewater (Table S10).…”
Section: Normalization Of Wastewater Targets To Adjust For Fecal Contentmentioning
confidence: 99%
“…For COVID-19 WBE to be useful for public health decision-making, a better understanding is needed of the variability of SARS-CoV-2 in wastewater and how it relates to the true incidence or prevalence of COVID-19 in the contributing population (McClary-Gutierrez et al, 2021). Sources of target signal variability in wastewater include inconsistencies in sample collection and laboratory processing (Ahmed et al, 2020d;Feng et al, 2021), nucleic acid degradation based on travel time and conditions in the sewer (Hart and Halden, 2020a), and signal dilution due to rainfall and diurnal flow changes (Zahedi et al, 2021). Researchers have addressed some of these sources of variability through normalization to biomarkers, increased sampling frequency, processing biological replicates, and smoothing/forecasting (D'Aoust et al, 2021b;Feng et al, 2021;Graham et al, 2020;McLellan et al, 2021;Nemudryi et al, 2020;Stadler et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation